Ameliorating effects of palm oil mill effluent on the chemical properties of soils and maize growth in pots - Jusop, Shamsuddin; Ng, C. C.; Z., Ahmad Ruzaini (Universiti Putra Malaysia Press, 1995)
Highly weathered Malaysian soils are mostly acidic having high Al saturation and low Ca and/or l\1g contents. A leaching experiment in PVC columns and a pot trial were carried out to alleviate these acid soil infertilities by application of palm oil mill effluent (POME). The results of the leaching study showed that the topsoil pH, organic C and exchangeable Mg increased with increasing rate of POME application. Maize grew poorly on acidic Malaysian soils without any amendment. Relative plant top weight increased significantly as the pH (H2O and exchangeable Mg increased. On the other hand, the relative plant top weight decreased linearly as the exchangeable Al and Al saturation increased. With POME treatment, the critical pH (H20) for maize growth was 4.2 - 4.5, whereas the critical exchangeable Mg was 0.5 cmol/kg soil.